A low-power quadrature LO generator with mutual power-supply rejection technique - Zhou, Ao (2021)
This paper presents a supply-insensitive low-power quadrature local oscillation (LO) generator based on the current-reused voltage-controlled oscillator (VCO) and divide-by-two frequency divider (FD). By utilizing the mutual power-supply rejection (M-PSR) technique, a voltage regulator is embedded into the FD to provide a supply-insensitive voltage for VCO. Meanwhile, the feedback loop provides a supply-insensitive current and time constant compensation for FD. The M-PSR technique does not require extra voltage headroom, thus the proposed quadrature LO generator can work under the supply of 0.9 V. A prototype of the proposed quadrature LO generator is implemented in a 28-nm CMOS process. Measurement results indicate that the LO generator achieves a phase noise of -110.5 dBc/Hz@1MHz at the carrier of 5.9 GHz and the power consumption is 1.8 mW. This work has a competitive figure of merit in supply sensitivity or in area (FOMss or FOMa respectively) among the state-of-the-art works.